Utilization of Araceae by local community in Cisoka Village, Cikijing Sub-district, Majalengka District, West Java, Indonesia - ASEP ZAINAL MUTAQIN; MUTHI FATHARANI; JOHAN ISKANDAR; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2018)
Mutaqin AZ, Fatharani M, Iskandar J, Partasasmita R. 2018. Utilization of Araceae by local community in Cisoka Village,  Cikijing Sub-district, Majalengka District, West Java, Indonesia. Biodiversitas 19: 640-651. Various species of Araceae plants are widely used by the tribes of Sunda as food. However, cultivation is increasingly rare inWest Java region, and is found in some places only. One area where many people still grow Araceae plants is Cisoka Village, Cikijing Sub-district, Majalengka District, West Java Province, Indonesia. This paper aims to explain the reason for the cultivation of Araceae by the local community in the Village of Cisoka. This study used a combination of qualitative and quantitative methods, but the former was used more than the latter The primary data were collected through structured and semi-structured interviews, participant observation, exploration, and plant sample collection. The data were analyzed descriptively with emic and ethic approaches. The results of the study showed that 20 species and 13 varieties (landraces) of Araceae plants were used by the community. The parts of plant traditionally used by the commumity were tuber, petiole, and leaf. The utilization of the Araceae plants were categorized into 4 main functions, namely, as food, medicine, decoration, and fish feed. The species of Araceae were commonly cultivated in various agroecosystem types, mainly home gardens, gardens, and rice fields.